A pilot study of a wearable apnoea detection device. Issue 10 (3rd October 2014) - Rodriguez-Villegas, Esther; Chen, Gwangwei; Radcliffe, Jeremy; Duncan, John
Abstract : Rationale: Current techniques for monitoring patients for apnoea suffer from significant limitations. These include insufficient availability to meet diagnostic needs, cost, accuracy of results in the presence of artefacts and difficulty of use in unsupervised conditions. Objectives: We created and clinically tested a novel miniature medical device that targets overcoming these limitations. Methods: We studied 20 healthy control participants and 10 patients who had been referred for sleep apnoea diagnosis. The performances of the new system and also of the Food and Drug Administration (FDA) approved SOMNO clinical system, conventionally used for sleep apnoea diagnosis were evaluated under the same conditions. Both systems were tested during a normal night of sleep in controls and patients. Their performances were quantified in terms of detection of apnoea and hypopnoea in individual 10 s epochs, which were compared with scoring of signals by a blinded clinician. Main results: For spontaneous apnoeas during natural sleep and considering the clinician scorer as the gold standard, the new wearable apnoea detection device had 88.6% sensitivity and 99.6% specificity. In comparison the SOMNO system had 14.3% sensitivity and 99.3% specificity. The novel device had been specifically designed to detect apnoea, but if apnoea and hypopnoea during sleep were both considered in the assessment, the sensitivity and specificity were 77.1% and 99.7%, respectively, versus 54% and 98.5%, respectively, for the SOMNO. Conclusions: The performance of the novel device compares very well to the scoring by an experienced clinician even in the presence of breathing artefacts, in this small pilot study. This can potentially make it a real solution for apnoea home monitoring.